The FLRW Universe Metric in 4+1 Spacetime Dimensional with Spherical Coordinate Invariance - Rangga Prasetya Alamsyah; Meini Aninda (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2021)
The Friedmann-Lemaître-Robertson-Walker (FLRW) universe metric is an abstraction of the distance between two points in a time-evolving universe. The evolution of the FLRW universe can be either expansion or contraction. In this article, the FLRW universe metric in 4+1 spacetime is formulated. When this metric is relatively one dimension higher than the original metric. The addition of these dimensions is based on the assumption that the laws of physics have the same shape in the higher dimensions. A mathematical modeling idea is based on a spatial 4-dimensional isotropic sphere system immersed in this 5-dimensional spatial system. Then, Minkowski’s flat spacetime concept was used to couple the spatial dimensions with the temporal dimension. Thus, we find the FLRW universe metric in 4+1 spacetime. The result of formalism shows that there is a radius quantity in the extra metric dimension, and this radius quantity forms the angle with the other two spatial dimensions. Then, we also show that the dimension of the cosmic scale factor will always be relatively higher than the spatial dimension of the metric. This has implications for the expansion or contraction of the FLRW universe model which remains valid in high dimensions.